(The Effect of Glucose and Potassium Sorbate Addition on The Processing of Dodol) - Sardjono - (Warta Industri Hasil Pertanian, 1990)
A study on the effect of glucose and potassium sorbate addition on the processing of "dodol" had been carried out. The treatment done were glucose 1% and storage (0,1,2,3,4,5, and 6 months).The moisture content, hard layer thickness, mold, yeast and total aerobic plate count (TPC) were observed during 6 months storage.The result showed that the use of glucose 1% inhibit the hard layer growth of "dodol" whereas the addition of potassium sirbate 0.2% retain the "dodol" quality for 4 - 5 months. After 6 months storage, the moisture content was 14.69 - 16.18%, hard layer thickness 0.1 - 1.63 mm, mold 0 - 43 colony per g, yeast 0 colony per g and total aerobic plate count 10-3.30 x 10 colony per g.